Pelajaran Pendidikan Agama Islam Melalui Media Audio Visual Kelas VII SMPLB Tunagrahita di SLB Negeri 2 Padang - Setiawan, Agus (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of students with intellectual disabilities in class VII through the implementation of audio-visual media in Islamic Religious Education (PAI) learning. This research uses a Classroom Action Research (CAR) approach conducted in two cycles. In the first cycle, the students’ learning outcomes showed that, although most students scored average and below-average grades, the application of audio-visual media increased student participation and motivation in learning. After reflection and improvements in the second cycle, the students’ learning outcomes significantly increased, with all students achieving good scores. Based on these findings, it can be concluded that audio-visual media is effective in enhancing students’ understanding of zakat and zakat fitrah materials